Real wave packet and flux analysis studies of the H+F2 ? HF+F reaction - Gogtas, Fahrettin; Karabulut, Ezman; Tanaka, Tomokazu; Takayanagi, Toshiyuki; Tutuk, Rukiye (Wiley, 2012)
The H + F2 ? HF + F reaction on ground state potential energy surface is investigated using the quantum mechanical real wave packet and Flux analysis method based on centrifugal sudden approximation. The initial state selected reaction probabilities for total angular momentum J = 0 have been calculated by both methods while the probabilities for J > 0 have been calculated by Flux analysis method. The initial state selected reaction probabilities, integral cross sections and rate coefficients have been calculated for a broad range of collision energy. The results show a large rotational enhancement of the reaction probability. Some resonances were seen in the state-to-state reaction probabilities while state-to-all reaction probabilities and the reaction cross section do not manifest any oscillations and the initial state selected reaction rate constants are sensitive to the temperature. (c) 2011 Wiley Periodicals, Inc. Int J Quantum Chem, 2012
Keywords: reactive scattering; wave packet study; reaction probabilities; cross sections; rate constants